Perceiving the Monsters' Portrayal of Scottish Kelpie and Indonesian Baru Klinting through Material Ecocriticism - Benedicta Angie Azaria Prasetyo Rahayu; Raden Roro Rachma Amalia Putri; Jardin Urbania Basundoro; Alvanita Alvanita (English Letters Department, Faculty of Letters, Universitas Sanata Dharma, 2026)
Not only fosters local wisdom, folklore also promotes sustainable eco-friendly tourism by embedding cultural beliefs that support nature preservation. Among the many elements of nature represented in folklore, water occupies a distinctive place, often represented in folklore through water-linked beings that embody both danger and protection. However, there has been limited research on how water monsters in folklore function as symbols of ecological awareness and preservation, which reveals the relationship between human and nature. This article addresses the gap by examining two children’s stories adapted from Scottish and Indonesian folklore. This study employed a comparative qualitative textual analysis of two stories, The Secret of the Kelpie (2022) and Legenda Baru Klinting (2018). Material ecocriticism was used to provide the analytical framework, focusing on the concepts of agency, narrativity, entanglement, and non-linear causality. Relevant passages were coded and compared to examine how these narratives represent human–water relations and ecological responsibility. This research shows how Kelpie and Baru Klinting, as monstrous figures, embody ecological narratives through their forms, with water itself acting as a non-human entity and meaning maker. At the same time, cultural objects such as iron and lesung function as protective symbols used to ward off evil spirits. From an educational perspective, the interaction between humans and nature in these stories teaches children to recognize the hidden dangers beneath the water. In a broader context, the findings suggest that folklore can serve as a medium for preserving awareness of the aquatic environment.